Potential osmotic and hormonal priming for higher productivity of rice - Kareem, Isiaka; Ismail, Mohd Razi; Puteh, Adam; Abdul Rahim, Anuar; Habib, Sheik Hasna; Kausar, Hossain (WFL Publisher, 2013)
A study was conducted to evaluate the efficiency of different priming media for enhancing growth and development of MR219 rice in Malaysia. Different osmotic salts and plant hormones were used as priming media at four concentrations. In osmopriming experiment, the significantly highest tiller number per hill was recorded in treatments T19 (pre-germination) and T16 (PEG at concentration of 40) which were 43% and 38% higher over control whereas in hormone priming, the significantly highest tiller number was recorded in treatment T19 (salicylic acid at 150 ppm) which was 53% higher over control. In osmotic priming media, the highest number of productive tillers per hill was recorded in treatments T16 which was 82% higher above control and in plant hormone, the significantly highest number of productive tillers was recorded in treatment T19 suggesting osmotic priming treatment T16 (PEG at 40%) and hormone priming treatment T19 (salicylic acid at 150 ppm) have the potential to be used as priming media for higher productivity of MR219 rice in Malaysia.